PERAN PERPUSTAKAAN DALAM MENINGKATKAN LITERASI SISWA MELALUI PENDAMPINGAN MEMBACA DI SDK NUABOSI - Veronika Tuga; Konsntantinus Dua Dhiu; Andi Nafsia (ADIBA : JOURNAL OF EDUCATION, 2025)
Literacy is one of the important things in the world of education, especially in language. One of the effective things in improving literacy skills for students is to carry out reading assistance activities by utilizing the library room. This activity aims to determine the literacy skills possessed by students at SDK Nuabosi, with data collection methods using observation, interview and documentation activities, this activity was carried out targeting grade 3 students with a total of 27 students. The results of the observations made found that the use of the library room at SDK Nuabosi was still ineffective which caused students' literacy skills to be low. This is because the library room at SDK Nuabosi was closed in 2019 due to the corona virus outbreak. The library was reopened by students of the 6th batch of teaching campuses at SDK Nuabosi with the permission of the principal and the school, KM students carried out a work program where the work program was carried out with the help of students and teachers at the school. These activities include cleaning the environment and unkempt library rooms, sorting reading books and providing reading assistance to students. The arrangement of the library room aims to increase students' interest in reading and provide a comfortable reading space for students while the reading assistance activities carried out aim to provide motivation to students in improving their literacy skills. The library has a very important role for the school environment where the existence of the library helps students in reading, searching for information and helps the effectiveness of the teaching and learning process at school.